Analisis Panic Buying dan Hoarding Behavior Konsumen dalam Menghadapi Isu Kelangkaan BBM di Kotamadya Pontianak: Pendekatan Kuantitatif dengan Uji Mann-Whitney dan Kruskal-Wallis - Mardiyati; Hijrah Wahyudi (Jurnal Ekonomi STIEP, 2026)
This study examines panic buying and hoarding behavior among fuel consumers in Pontianak Municipality in response to scarcity rumors. Using a quantitative approach with a survey method, data were collected from 150 respondents selected through purposive and accidental sampling at gas stations across six sub-districts. The analysis employed Mann-Whitney and Kruskal-Wallis tests to compare behavioral scores across demographic and situational characteristics. The findings reveal that male consumers exhibit significantly higher panic buying scores than females (p = 0.017). Income level also differentiates panic buying behavior, with the highest income group showing the highest scores (p = 0.017). Vehicle type emerges as the strongest determinant, where private car and commercial vehicle users demonstrate significantly higher panic buying compared to small motorcycle users (p = 0.002). No significant differences are found across sub-districts, indicating that scarcity rumors spread evenly throughout the municipality. Hoarding behavior is strongly associated with prior experience of purchasing fuel using jerry cans (p < 0.001) but shows no relationship with income. Trust in circulating rumors and anxiety triggered by information serve as key psychological drivers. The study recommends that local government and Pertamina strengthen crisis communication strategies and public literacy to mitigate the impact of unverified scarcity rumors.